Decision Support Systems on Complex Situation Governance Based On Scenario Approach - V. Chernov, I; I. Makarenko, D (International Journal of Engineering and Technology, 2018)
Governance of modern situations arising in regional systems requires the development of distributed decision support systems in governance network. The paper proposes a strategic decision support scheme based on a combination of tools supporting the process of constructing multifactor situation models, and agreed models, taking into account different stakeholdersâ€™ opinions, scenario analysis tools for forecasting and searching for control actions as well as tools for monitoring situation change by factors. At an acceptable level of maturity of technologies of structuration and formalization of knowledge about the situation in the form of models, the means of supporting scenario analysis and synthesis of control activities on complex situations are critical.Â Â